1980
DOI: 10.1007/bf03348245
|View full text |Cite
|
Sign up to set email alerts
|

Painless thyroiditis followed by autoimmune disorders of the thyroid. A case report with biopsy

Abstract: Painless thyroiditis is a clinical entity of unknown origin. We report a case of a woman first seen with painless thyroiditis, who consequently developed a true hyperthyroidism, then exophthalmos and finally permanent hypothyroidism. The biopsy findings and serum antibodies determinations at the final stage were of Hashimoto's thyroiditis. The case is discussed and the need for a long follow-up after a painless thyroiditis is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…In contrast to all of the above reported cases, [4][5][6][7][8] our patient experienced two consecutive episodes of hyperthyroidism following PPT. Her first episode occurred 12 months after her first delivery and the recurrent hyperthyroidism occurred 8 months after recovery.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In contrast to all of the above reported cases, [4][5][6][7][8] our patient experienced two consecutive episodes of hyperthyroidism following PPT. Her first episode occurred 12 months after her first delivery and the recurrent hyperthyroidism occurred 8 months after recovery.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast to the high incidence of PPT or recurrence of GD in the postpartum period in women with a history of GD, 2,10) the development of endogenous hyperthyroidism in patients with a history of PPT, as in our case, is infrequent; however, it has been reported previously in the literature. [4][5][6][7][8] These patients were first diagnosed with PPT within six months after delivery, and subsequently developed GD after PPT (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (Iitaka et al, 1998) and others (Strakosch et al, 1978;Werner, 1979;Wall et al, 1982;Tamai et al, 1991) have previously reported that apparently normal people can produce TSHR Abs after destruction of the thyroid gland by subacute thyroiditis. In fact, previous reports have demonstrated the development or exacerbation of GD following the onset of PT (Sartani et al, 1980;Taylor et al, 1982;Iitaka et al, 1991;Sarlis et al, 1997;Shorey et al, 1998). PT has a destructive effect on the thyroid gland, which may trigger the production of TSHR Abs resulting in the development or exacerbation of GD.…”
Section: Discussionmentioning
confidence: 96%
“…The development of ST in patients with a history of GD appears to be common during the postpartum period (11,12), but has also been documented in nonpregnancy related cases (13). The development of GD with a history of ST however, appears to be far less common (14,15). In these cases, it is possible that the release of thyroidal antigens during the destructive process triggers GD in a genetically susceptible individual (4,16).…”
Section: Introductionmentioning
confidence: 90%